Origin of ultralow Young׳s modulus in a metastable β-type Ti–33Nb–4Sn alloy. (June 2016) - Hou, Y.P.; Guo, S.; Qiao, X.L.; Tian, T.; Meng, Q.K.; Cheng, X.N.; Zhao, X.Q.
Abstract: Although there is difficulty in growing a Ti–33Nb–4Sn single crystal due to its ultralow β-phase stability, the single-crystal elastic constants of metastable β-type Ti–33Nb–4Sn (wt%) alloy were extracted successfully from its polycrystal by in-situ synchrotron X-ray diffraction technique, to clarify the origin of the ultralow Young's modulus in its polycrystal. It is indicated that compared to binary TiCr, TiV and TiNb alloys, the Ti–33Nb–4Sn alloy possesses slightly lower β-phase stability with respect to {110}<110> -         shear (i.e., C ׳) but much lower β-phase stability regarding to {001}〈100〉 shear (i.e., C44 ). An analysis by the Hill approximation suggests that the ultralow isotropic polycrystalline Young׳s modulus ( E H ) of Ti–33Nb–4Sn alloy originates from the extremely low shear modulus C44 as well as the relatively low C ׳. This indicates that in addition to C ׳, C44 has a significant contribution to the Young's modulus of polycrystal, which challenges a conventional understanding that the Young's modulus of β-type Ti alloys is predominantly determined by C ׳.